TINGKAT PENGETAHUAN PESERTA SERTIFIKASI PEMBIMBING MANASIK HAJI PROFESIONAL: CATATAN ANGKATAN VI DARI SEMARANG - Sattar, Abdul; Hasanah, Hasyim (Multazam : Jurnal Manajemen Haji dan Umrah, 2023)
The focus of this research is to see whether the Professional Hajj Manasik Guide Certification program is just a ceremonial activity (certificate orientation) or it is really a program that qualitatively produces prospective professional Hajj Manasik Guides. To obtain results regarding the level of knowledge, this research used a quantitative research method of the type of field research originating from pre-test and post-test documents of 81 participants in the batch IV 2019 certification program. The data were then analyzed using descriptive statistics and inferential statistics t-test using the SPSS program assistance 23.0 for windows. There are two findings that can be put forward as a result of this research. First, the level of understanding of the certification participants after attending the program was in the high criteria, namely between a score of 74-81 with a percentage of 45.5% for 37 participants. This confirms that the certification activity succeeded in increasing the participants' knowledge. Second, the hypothesis which states the level of knowledge of the certification training participants is empirically proven to be accepted, positive, and significant with the t-test.